2022
DOI: 10.1002/adhm.202200955
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of PD‐L1‐Derived Phosphorylation‐Mimicking Peptides by Engineered Biomimetic Nanovesicles to Enhance Osteosarcoma Treatment

Abstract: Osteosarcoma is a rare malignant bone-originating tumor that usually occurs in young people. Programmed cell death 1 ligand 1 (PD-L1), an immune checkpoint protein, is highly expressed in osteosarcoma tissues. Several recent studies have indicated that the tumor-related role of PD-L1 in tumors, especially non-plasma membrane (NPM)-localized PD-L1, is not limited to immune regulation in osteosarcoma. Here, mass spectrometry analysis is combined with RNA-seq examination to identify the intracellular binding part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There is no doubt that peptide-based nanostructures have increased exponentially over the past few decades, which is attributed to their bio-inspired properties. Biomimetic strategies have been widely used in various types of research, such as tumor therapy ( He et al, 2022 ; Peng et al, 2022 ; Wu et al, 2022 ), vaccination ( Peng et al, 2022 ) and wound dress ( Mirhaj et al, 2022 ). And it has been reported that nanocarriers with bionic cell membranes were an effective and safe delivery system for osteosarcoma therapy ( Huang and Kiick, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that peptide-based nanostructures have increased exponentially over the past few decades, which is attributed to their bio-inspired properties. Biomimetic strategies have been widely used in various types of research, such as tumor therapy ( He et al, 2022 ; Peng et al, 2022 ; Wu et al, 2022 ), vaccination ( Peng et al, 2022 ) and wound dress ( Mirhaj et al, 2022 ). And it has been reported that nanocarriers with bionic cell membranes were an effective and safe delivery system for osteosarcoma therapy ( Huang and Kiick, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment of OS is still quite limited ( Sergi, 2021 ). Current conventional treatments for malignancy are chemotherapy, radiation therapy, and surgical resection ( Wu et al, 2022a ). Surgery can only remove the local tumor, but cannot cure the metastasis ( Zhu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of nanomedicine, nanomaterials offer new opportunities to improve drug delivery and reduce their adverse effects ( Xia et al, 2022a ). Nanoexamples are widely used in the immunotherapy of tumors using their unique size, charge properties, and targeting properties ( Wu et al, 2022a ). The enhanced permeability retention (EPR) properties of tumor cells allow nanoparticles to remain in the tumor microenvironment for a long time ( Morales-Orue et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%